Stakeholder communication and client understanding of viral load suppression in Blantyre, Malawi - what role did U = U play before the flip the script campaign? - Berner-Rodoreda, Astrid; Chione, Boniface; Ngwira, Esther; Dambe, Rosalia; Phiri, Sam; Bärnighausen, Till; Alhassan, Yussif; Taegtmeyer, Miriam; Tembo, Petros; Feldacker, Caryl; Kiruthu-Kamamia, Christine; Neuhann, Florian (PLOS ONE, 2025)
Background Various studies have demonstrated the effectiveness of viral load suppression (VLS) in preventing sexual transmission of the human immunodeficiency virus (HIV), leading to the slogan “Undetectable = Untransmittable” or “U = U”. As few studies have examined health stakeholders’ understandings of U = U, the communication of a suppressed viral load (VL) to male clients, and male clients’ understandings of the benefits of a suppressed VL in Sub-Saharan Africa, we explore these in this study. In the field of HIV, it is only in recent years that men who have sex with women (MSW) have been given some attention. The treatment cascade shows that MSW lag behind women in knowing their HIV-status, accessing treatment and suppressing their VL. Methods and findings Our findings are based on in-depth qualitative semi-structured in-person interviews with 16 local stakeholders (health facility personnel, NGO and church-based HIV programme implementers and applied researchers) and 39 men on antiretroviral treatment (ART) in Blantyre, Malawi: Twenty-three men with a detectable VL and 16 with a suppressed VL were included in the study. Thematic analysis of the audio-recorded and transcribed interviews show that stakeholders were mostly unfamiliar with the slogan U = U. Despite realizing the advantages for clients and their partners, stakeholders were cautious about how they conveyed information about an undetectable VL: they were worried about clients either misinterpreting an undetectable VL as being cured of HIV or engaging in risky sexual behaviour. This attitude prevailed irrespective of the degree of stakeholders’ endorsement of the evidence of U = U. Male clients were aware of personal health benefits of a suppressed VL, yet unaware of their non-infectiousness. In order not to infect others, some men ceased sexual relations or forwent procreation. Conclusion For U = U to become part of a client’s actionable knowledge with regard to treatment benefits, U = U needs to be communicated comprehensively. To what extent recent policy changes, the Flip the Script campaign to make U = U known and staff training programs have led to a different practice will need to be further researched, using our findings as a reference point. Integrated health services are already in place; however, VL monitoring, and testing and treatment for sexually transmitted infections (STIs) should ideally be conducted more frequently than annually, so that Malawian clients can be assured of their VL status and of not passing on the virus while also being able to get any STIs treated.